2023
DOI: 10.3390/ijms24044067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Light Chain as Biomarker for Cladribine-Treated Multiple Sclerosis Patients in a Real-World Setting

Abstract: Serum neurofilament light chain (sNfL) is an intensely investigated biomarker in multiple sclerosis (MS). The aim of this study was to explore the impact of cladribine (CLAD) on sNfL and the potential of sNfL as a predictor of long-term treatment response. Data were gathered from a prospective, real-world CLAD cohort. We measured sNfL at baseline (BL-sNfL) and 12 months (12Mo-sNfL) after CLAD start by SIMOA. Clinical and radiological assessments determined fulfilment of “no evidence of disease activity” (NEDA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…ARR, disability progression (by EDSS, T25FW, and 9HPT), and MRI activity at 12 months were not associated with sNfL levels at baseline. The MRI finding of Gd+ lesions at OCR onset was moderately correlated with baseline sNfL levels (0.458. p=0.012), in line with the study by Cross et al [23] NEDA-3 was reached in 70% of the PwMS, very similar to other results obtained using highefficacy DMTs [31,44]. After 12 months of OCR treatment, the ARR was reduced in 83%, the EDSS was maintained, and there was an 80% reduction in those with radiological activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…ARR, disability progression (by EDSS, T25FW, and 9HPT), and MRI activity at 12 months were not associated with sNfL levels at baseline. The MRI finding of Gd+ lesions at OCR onset was moderately correlated with baseline sNfL levels (0.458. p=0.012), in line with the study by Cross et al [23] NEDA-3 was reached in 70% of the PwMS, very similar to other results obtained using highefficacy DMTs [31,44]. After 12 months of OCR treatment, the ARR was reduced in 83%, the EDSS was maintained, and there was an 80% reduction in those with radiological activity.…”
Section: Discussionsupporting
confidence: 89%
“…The significant reduction in sNfL levels verifies the molecular effect of OCR on neurodegeneration in PwMS and was observed at three months after the first infusion, earlier than reported for other DMTs [27]. The 16% decrease in sNfL levels at 12 months was lesser than described in the OBOE study with OCR [23] or in the study with CLD [31].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Cladribine tablets were also able to regulate the serum neurofilament (sNfL) levels, a marker with a key role in both monitoring treatment response and capturing long-term disease outcomes [ 69 , 70 ]. Data from the MAGNIFY-MS study and real-world cohorts showed a significant reduction of sNfL as early as 6 months after the initiation of treatment with cladribine tablets that was maintained for up to 2 years [ 13 , 71 , 72 ]. Beyond that, further analyses of MAGNIFY-MS data have investigated the association between changes in sNfL levels and MRI outcomes in patients stratified as (1) no, (2) residual, or (3) resolved CUA lesions.…”
Section: Magnify-ms Study: a Look At The Onset Of Action Of Cladribin...mentioning
confidence: 99%
“…Annual immunophenotyping to monitor memory B cells may therefore provide another predictive marker of future MS disease activity [ 85 , 86 ]. CladT has been shown to reduce serum neurofilament light chain (sNfL), a biomarker of axonal damage in MS, although further validation of this biomarker is needed to predict who may need re-treatment with CladT [ 87 ].…”
Section: Patient Management After Initiation Of Cladribine Tabletsmentioning
confidence: 99%